Oral administration of red rice (Oryza nivara) bran extract reduced weight, visceral fat and liver steatosis amount in obesity male wistar rats (Rattus norvegicus) - Dianika Putri Puspitasari; Alex Pangkahila; Ni Nyoman Ayu Dewi (Indoscholar, 2021)
Background: Nonalcoholic fatty liver disease (NAFLD) is associated with obesity. Red rice (Oryza nivara) bran known to contain polyphenol and antioxidant that might be potential in reducing body weight and visceral fat in obese mice and preventing liver steatosis. This study was aimed to prove the effect of oral administration of red rice bran (Oryza nivara) extract on body weight, visceral fat, and liver steatosis amount in obese male Wistar rats. Method: In this research, the subjects were 36 male obese (Lee index > 0.3) white rats (Rattus norvegicus) Wistar strain, 4-5 months old, divided into two groups. The control group received placebo and the treatment group received 460mg/200gram red rice bran extract for 5-weeks. Body weight, visceral fat, and the amount of liver steatosis were observed. Differences between groups in each variable were analyzed. Results: The weight of the control group and the treatment group was 321.17 ± 19.04 grams and 305.72 ± 12.89 grams (p < 0.05). The visceral fat weight was 3.15 ± 0.34 grams in the control group and 2.99 ± 0.34 grams (p > 0.05) in the treatment group. Liver steatosis amount was 41 ± 18 cells per visual field in the control group, and 21 ± 12 (p < 0.05) in the treatment group. Conclusion: Oral administration of red rice bran extract can reduce body weight and liver steatosis amount in obese Wistar rat. The extract of red rice bran was not have a significant effect in reducing visceral fat.